THE EVALUATION OF REMOTE WORKING USING CIPP INDICATORS, A STUDY AT PT KARYA KAYA BAHAGIA (harisenin.com) - Prasetio Febiantono Saputra; Deden Sutisna (Journal of Economic, Bussines and Accounting (COSTING), 2024)
In this digital era, remote working systems have been adopted by many companies due to their flexibility and efficiency, despite some implementation shortcomings. This study aims to evaluate the remote working system at PT Karya Kaya Bahagia (harisenin.com) using the CIPP (context, input, process, product) evaluation model. Based on its objectives, this research is descriptive-evaluative with a qualitative approach. Descriptive-evaluative research provides in-depth insights into a phenomenon or program and assesses its effectiveness and impact. The approach is based on post-positivist philosophy, conducted in a natural setting with the researcher as the key instrument, using qualitative data collection techniques (observation, interviews, and documentation), and data analysis with the interactive model by Miles and Huberman. The remote working system at PT Karya Kaya Bahagia offers flexibility, reduces operational costs, and enhances employee satisfaction. However, challenges in coordination, communication, and technical issues such as unstable internet connections hinder work effectiveness. The CIPP evaluation reveals that while this system is effective in saving costs and providing flexibility, problems like suboptimal SOP implementation, weak supervision, and communication issues need resolution. Technical difficulties and inefficient time management also reduce productivity, and performance assessments based on OKR have not yet met expectations. To boost effectiveness and employee well-being, improvements are needed in transparency, communication, work methods, and compensation.